2019
DOI: 10.1002/ijc.32186
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypes of pancreatic ductal adenocarcinoma: Meta‐analysis of transcriptional subtypes

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is the most common malignancy of the pancreas and has one of the highest mortality rates of any cancer type with a 5‐year survival rate of <5%. Recent studies of PDAC have provided several transcriptomic classifications based on separate analyses of individual patient cohorts. There is a need to provide a unified transcriptomic PDAC classification driven by therapeutically relevant biologic rationale to inform future treatment strategies. Here, we used an integrative met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 59 publications
(162 reference statements)
3
49
0
Order By: Relevance
“…Importantly, we have verified the correlation between TP63 and IL1A expression in three independent transcriptome studies of human PDA tumors. In addition, a recent transcriptome study of human tissue samples revealed a correlation between squamous subtype PDA tumors and inflammation-associated changes in the stroma, which validates that our observations in experimental models are in accord with clinical observations (de Santiago et al, 2019). While the aberrant expression of TP63 confers a myriad of tumor cell-intrinsic phenotypes in PDA, such as enhanced motility, invasion, and resistance to cytotoxic chemotherapy (Danilov et al, 2011;Somerville et al, 2018), our work points to a powerful non cell-autonomous effect of TP63 in PDA in promoting inflammation.…”
Section: Discussionsupporting
confidence: 87%
“…Importantly, we have verified the correlation between TP63 and IL1A expression in three independent transcriptome studies of human PDA tumors. In addition, a recent transcriptome study of human tissue samples revealed a correlation between squamous subtype PDA tumors and inflammation-associated changes in the stroma, which validates that our observations in experimental models are in accord with clinical observations (de Santiago et al, 2019). While the aberrant expression of TP63 confers a myriad of tumor cell-intrinsic phenotypes in PDA, such as enhanced motility, invasion, and resistance to cytotoxic chemotherapy (Danilov et al, 2011;Somerville et al, 2018), our work points to a powerful non cell-autonomous effect of TP63 in PDA in promoting inflammation.…”
Section: Discussionsupporting
confidence: 87%
“…To further understand to what extent immune cells and nerve fibers may interact, each routine H&E slide was scored manually into a lymphocyte-predominant, neutrophil-predominant or immune-cell-depleted phenotype [ 22 ]. The scoring was done by a senior pathologist and the Ph.D. and based on the most dominant immune cell on one tumor slide only by viewing the histology on HE staining.…”
Section: Resultsmentioning
confidence: 99%
“…The CD8 + T-cells were defined as the remaining clusters which co-express CD8A and CD8B . The following filters were used for cluster definitions of validated cell populations: Tregs (positive expression of FOXP3 ); Senescent (negative expression of CD27 and CD28 , positive 75 th percentile expression of KLRG1 and positive mean expression of B3GAT1 ); Exhausted (positive 75 th quantile expression of ≥ 4 of HAVCR2, PDCD1, TOX, LAG3, CTLA4, TIGIT, CD38, ENTPD-1 and positive expression of TRDC was filtered out to exclude gamma-delta T-cells).…”
Section: Methodsmentioning
confidence: 99%
“…Early diagnosis with surgical resection followed by combination chemotherapy offers the best chance of long-term survival (2). We and others have shown that the immune infiltrate in the primary pancreatic tumour is prognostic of the clinical course after a surgical resection (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation